Noise-Induced Hearing Loss: Updates on Molecular Targets and Potential Interventions - Huanyu Mao; Yan Chen (Neural Plasticity)
Noise overexposure leads to hair cell loss, synaptic ribbon reduction, and auditory nerve deterioration, resulting in transient or permanent hearing loss depending on the exposure severity. Oxidative stress, inflammation, calcium overload, glutamate excitotoxicity, and energy metabolism disturbance are the main contributors to noise-induced hearing loss (NIHL) up to now. Gene variations are also identified as NIHL related. Glucocorticoid is the only approved medication for NIHL treatment. New pharmaceuticals targeting oxidative stress, inflammation, or noise-induced neuropathy are emerging, highlighted by the nanoparticle-based drug delivery system. Given the complexity of the pathogenesis behind NIHL, deeper and more comprehensive studies still need to be fulfilled.